Antioxidant Activity of Fresh Decinte, Fresh Sari, and Fresh Ethanol Extract of Soursop (Annona muricata L.) Leaves Using DPPH Method - Fransiska, Eva; Daulay, Anny Sartika; Ridwanto, Ridwanto; Yuniarti, Rafita (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
Antioxidants are compounds that are able to ward off or reduce free radicals in the body so that they can prevent several diseases. Soursop leaves (Annona muricata L.) are used as a traditional herbal medicine to prevent or treat cancer, as well as a natural antioxidant, which is usually used by people by boiling it. The purpose of this study was to look at the phytochemical screening by comparing fresh boiled water, fresh juice, and a fresh extract of soursop leaves, as well as test the antioxidant activity with the addition of DPPH (1,1-diphenyl-2-picrylhydrazyl) and measured using a UV-Vis spectrophotometer at 516 nm. The results of the soursop leaf phytochemical screening showed that there were groups of chemical compounds such as flavonoids, glycosides, tannins, and saponins. The results of testing the antioxidant activity by looking at the maximum wavelength of DPPH, using a UV-Vis spectrophotometer, obtained IC50 values for fresh juice of 770.067 µg/mL, fresh decoction of 1,022.8422 µg/mL, and ethanol extract of 299.733 µg/mL. Based on the results of the study, it was shown that the ethanol extract had stronger antioxidant activity than a fresh decoction and the fresh juice of soursop leaves.